(untitled) - Deitel, Harvey M. (Upper Saddle River, N.J., 2000)
A text outlining every aspect of e-commerce, for professional managers. Introduces e-business, e-commerce, the Internet, and the World Wide Web, covering such topics as online monetary transactions, Internet security, e-customer relationship management, online industries, online banking and investment, and online career services. DLC: Electronic commerce.
Keywords: Electronic commerce,Business enterprises,Thương mại điện tử,Doanh nghiệp kinh doanh; Computer networks,Management; Mạng lưới máy tính; Quản lý